Grouping of tropical midaltitude maize inbred lines based on yield data and molecular markers - Menkir, A.; Melake-Berhan, A.; Ingelbrecht, I.L.; Adepoju, A. (Springer, 2004)
The classification of maize inbred lines into heterotic groups is an important undertaking in hybrid breeding. The objectives of our research were to: (1) separate selected tropical mid-altitude maize inbred lines into heterotic groups based on grain yield data; (2) assess the genetic relationships among these inbred lines using amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers; (3) examine the consistency between yield-based and marker-based groupings of the inbred lines. Thirty-eight tropical mid-altitude maize inbred lines were crossed to two inbred line testers representing the flint and dent heterotic pattern, respectively. The resulting testcrosses were evaluated in a trial at three locations for 2 years. Significant general combining ability (GCA) and specific combining ability (SCA) effects for grain yield were detected among the inbred lines. The tester inbred lines classified 23 of the 38 tested inbred lines into two heterotic groups based on SCA effects and testcross mean grain yields. This grouping was not related to endosperm type of the inbred lines. The outstanding performance of testcrosses of the remaining 15 inbred lines indicates the presence of significant genetic diversity that may allow the assignment of the lines into more than two heterotic groups. Diversity analysis of the 40 maize inbred lines using AFLP and SSR markers found high levels of genetic diversity among these lines and subdivided them into two main groups with subdivision into sub-groups consistent with breeding history, origin and parentage of the lines. However, heterotic groups formed using yield-based combining ability were different from the groups established on the basis of molecular markers. Considering the diversity of the genetic backgrounds of the mid-altitude inbred lines, the marker-based grouping may serve as the basis to design and carry out combining ability studies in the field to establish clearly defined heterotic groups with a greater genetic similarity within groups.